An Introduction to Item Response Theory for Patient-Reported Outcome Measurement - Nguyen, Tam H.; Han, Hae-Ra; Kim, Miyong T.; Chan, Kitty S. (The patient : patient-centered outcomes research, 2014)
The growing emphasis on patient-centered care has accelerated the demand for high-quality data from patient-reported outcome (PRO) measures. Traditionally, the development and validation of these measures has been guided by classical test theory. However, item response theory (IRT), an alternate measurement framework, offers promise for addressing practical measurement problems found in health-related research that have been difficult to solve through classical methods. This paper introduces foundational concepts in IRT, as well as commonly used models and their assumptions. Existing data on a combined sample ( n = 636) of Korean American and Vietnamese American adults who responded to the High Blood Pressure Health Literacy Scale and the Patient Health Questionnaire-9 are used to exemplify typical applications of IRT. These examples illustrate how IRT can be used to improve the development, refinement, and evaluation of PRO measures. Greater use of methods based on this framework can increase the accuracy and efficiency with which PROs are measured.